Vibration control of a structure with ATMD against earthquake using fuzzy logic controllers - Guclu, Rahmi; Yazici, Hakan (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2008)
In this paper, fuzzy logic and PD controllers are designed for a multi-degree-of freedom structure with active tuned mass damper (ATMD) to suppress earthquake-induced vibrations. Fuzzy logic controller (FLC) is preferred because of its robust character, superior performance and heuristic knowledge use effectively and easily in active control. A fifteen-degree-of-freedom structural system is modeled with two types of actuators. These actuators are installed on the first storey and fifteenth storey which has ATMD. The system is then subjected to Kocaeli Earthquake vibrations, which are treated as disturbances. In control, linear motors are used its the active isolators. At the end of the study, the time history of the storey displacements and accelerations, ATMD displacements, control voltages, frequency responses of the both uncontrolled and the controlled structures are presented. Performance of the designed FLC hits been shown for the different loads and disturbances using ground motion of the Kobe Earthquake. The results of the simulations show a good performance by the fuzzy logic controllers for different loads and the earthquakes. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: SLIDING-MODE CONTROL; Acoustics; Engineering; Mechanics